Emotional Labor and Customer Satisfaction: Emotional Regulation in Service Delivery - Nurul Fadhilah (TechTalent & Business Review, 2026)
Emotional labor has become a critical component in service-oriented organizations, where employees are required to manage and regulate their emotions to deliver quality service. This study aims to analyze the role of emotion regulation in emotional labor and its impact on customer satisfaction. A quantitative explanatory approach was employed, with data collected through structured questionnaires distributed to service employees and customers. The data were analyzed using descriptive statistics and regression analysis to examine the relationships between surface acting, deep acting, emotion regulation, and customer satisfaction. The findings reveal that deep acting has a positive and significant effect on emotion regulation and customer satisfaction, while surface acting has a negative effect. Emotion regulation is also found to significantly influence customer satisfaction, confirming its mediating role in the relationship between emotional labor and service outcomes. The discussion highlights that authentic emotional expressions enhance service quality through emotional contagion and perceived sincerity, whereas inauthentic expressions reduce customer trust and satisfaction. In conclusion, effective management of emotional labor requires organizations to promote deep acting and strengthen employees’ emotion regulation capabilities while providing organizational support to maintain employee well-being. These efforts are essential for achieving sustainable service performance and customer satisfaction